1991
DOI: 10.1177/153857449102500804
|View full text |Cite
|
Sign up to set email alerts
|

Distal Anastomotic Hyperplasia in Superficial Femoral-Popliteal Vein Femoropopliteal Bypass Grafts

Abstract: The incidence of distal anastomotic hyperplasia (DAH) in superficial femoralpopliteal veins (SF-PVs) used as femoropopliteal bypass (FPB) grafts was investigated, with particular reference to the form of distal anastomotic construction. Seventy-seven SF-PV grafts that met specific angiographic follow-up criteria qualified as "studied" grafts. DAH was identified in 13 (17%). Cobra head anastomoses, 2 cm or less in length, were used in 21 grafts and yielded 6 instances of DAH (29%). When 8 sharply tapered 3 cm (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
(3 reference statements)
1
3
0
Order By: Relevance
“…Although several of our patients have persistent swelling (a number that can be expanded or contracted depending on one's definition of persistent swelling), we have been quite satisfied with the minimal morbidity and durability of deep leg veins as primaty femoropopliteal bypass grafts. 4 The report from Providence does not contradict, and, in fact, actually supports, our experience.…”
Section: To the Editorssupporting
confidence: 73%
“…Although several of our patients have persistent swelling (a number that can be expanded or contracted depending on one's definition of persistent swelling), we have been quite satisfied with the minimal morbidity and durability of deep leg veins as primaty femoropopliteal bypass grafts. 4 The report from Providence does not contradict, and, in fact, actually supports, our experience.…”
Section: To the Editorssupporting
confidence: 73%
“…An association between anastomosis geometry and MIH has been demonstrated both in patient observation and in animal experiments. 13,14 Previous studies of cuffed anastomoses in vivo and in laboratory models have revealed specific flow patterns that occur consistently and periodically during the cardiac cycle. 15 It seemed likely that these flow patterns could minimize areas of low WSS and thus perhaps the development of MIH, but further experiments were required to quantify WSS.…”
mentioning
confidence: 99%
“…The need for extensive surgical dissection, need for preoperative venography, need for fasciotomy (w10%), risk of subsequent tibial-popliteal venous thrombosis (w10%), and being less familiar with the technique and the criteria for optimal patientvein selection are all associated to the low popularity of peripheral bypasses using FPVs. 3,4 Available preliminary results on use of FPVs may be encouraging, but we lack comparative studies, with the exception of the randomized trial by Shulman et al 5 comparing saphenous vein against FPVs for primary popliteal bypasses. They concluded that both conduits have similar patency and minimal morbidity.…”
Section: Replymentioning
confidence: 99%
“…Increasing experience and, we are sure, entering the "modern era" of FPB, were accompanied by increasingly better results, culminating in a 1991 report of significant primary and assisted primary patency rates of 84% and 91% at 5 years in 93 grafts. 3 Our early reports of inconsequential morbidity and saphenousequivalent patency were greeted with virtually unanimous disbelief. If Ali et al 4 had not used FPVs in complex aortic problems, our experience with their function and expendability might have remained unbelieved, unconfirmed, and essentially lost.We were confident FPV was expendable.…”
mentioning
confidence: 99%